2020
DOI: 10.1177/1526602819896293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IVUS-Derived Vessel Size on Midterm Outcomes After Stent Implantation in Femoropopliteal Lesions

Abstract: Purpose: To identify intravascular ultrasound (IVUS) findings that predict midterm stent patency in femoropopliteal (FP) lesions. Materials and Methods: A retrospective analysis was undertaken of 335 de novo FP lesions in 274 consecutive patients (mean age 72.4±8.2 years; 210 men) who had IVUS assessment before and after successful stent implantation. The mean lesion length was 13.2±9.8 cm. The primary outcome was primary patency at 24 months, defined as freedom from major adverse limb event (MALE) and in-sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The primary patency and freedom from restenosis rates following EVT were analyzed using the Kaplan-Meier method. The association between IVUS-evaluated dissection and the risk of restenosis was investigated using the Cox proportional hazards regression model with a phy have been identified using IVUS studies following implantation of bare nitinol stents and drug-eluting stents 9,10) . The superiority of IVUS over angiography in detecting dissection has been previously reported 11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary patency and freedom from restenosis rates following EVT were analyzed using the Kaplan-Meier method. The association between IVUS-evaluated dissection and the risk of restenosis was investigated using the Cox proportional hazards regression model with a phy have been identified using IVUS studies following implantation of bare nitinol stents and drug-eluting stents 9,10) . The superiority of IVUS over angiography in detecting dissection has been previously reported 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Female sex, diabetes, dialysis, critical limb ischemia, long lesion length, and poor run-off are known predictors of restenosis following self-expandable nitinol stenting for femoropopliteal lesions 20) . Another study used IVUS and reported that long lesion length, not taking cilostazol, and a small reference vessel diameter were associated with restenosis following selfexpandable nitinol stenting 9) . The Zephyr registry revealed that long lesion length, small distal reference vessel area, and small minimum stent area were predictors of restenosis following EVT with a drug-eluting stent 10) .…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Iida et al reported that IVUS use in femoropopliteal stenting appears to be associated not only with the procedure's success but also with a higher primary patency rate 56 . Previous reports were based on the IVUS evaluation methodology, such as vessel size, lumen area, wire route, calcification, lesion morphology, and vessel dissection after balloon angioplasty (Iida et al 2021;Kozuki et al 2021;Kurata et al 2020;Miki et al 2020a;Miki et al 2020b). Some parameters that influenced patency outcomes were shown, including calcification, vessel dissection, and post stent area and position (Iida et al 2015;Mori et al 2017;Norgren et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of difference in IVUS parameters between grades of dissection and the weak to moderate reliability revealed in the current study suggest that the current classification systems may be inadequate for reliably differentiating dissection severity. Recent studies have demonstrated that several IVUS parameters are independent predictors of clinical outcome of stenting in the femoropopliteal arteries 43,44 and IVUS may potentially be of similar use for identifying clinically important dissections. Further research in the form of adequately powered validation studies, including agreement testing, are required to establish if there are IVUS dissection parameters that can reliably predict poor clinical outcome.…”
Section: Inter-and Intra-observer Reliabilitymentioning
confidence: 99%